Difference between revisions of "009B Sample Midterm 2, Problem 5"

From Math Wiki
Jump to navigation Jump to search
Line 17: Line 17:
 
|-
 
|-
 
|
 
|
::You could use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -2px">u=\tan x.</math> Then, <math style="vertical-align: -5px">du=\sec^2(x)dx.</math>
+
::You could use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -2px">u=\tan x.</math> Then, <math style="vertical-align: -5px">du=\sec^2(x)dx.</math> Thus,
 
|-
 
|-
 
|
 
|
::Thus, <math style="vertical-align: -15px">\int \sec^2(x)\tan(x)~dx\,=\,\int u~du\,=\,\frac{u^2}{2}+C\,=\,\frac{\tan^2x}{2}+C.</math>
+
::<math>\begin{array}{rcl}
 +
\displaystyle{\int \sec^2(x)\tan(x)~dx} & = & \displaystyle{\int u~du}\\
 +
&&\\
 +
& = & \displaystyle{\frac{u^2}{2}+C}\\
 +
&&\\
 +
& = & \displaystyle{\frac{\tan^2x}{2}+C.}\\
 +
\end{array}</math>
 
|}
 
|}
  
Line 28: Line 34:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|First, we write <math style="vertical-align: -13px">\int \tan^4(x)~dx=\int \tan^2(x) \tan^2(x)~dx</math>.
+
|First, we write  
 
|-
 
|-
|Using the trig identity <math style="vertical-align: -5px">\sec^2(x)=\tan^2(x)+1</math>, we have <math style="vertical-align: -5px">\tan^2(x)=\sec^2(x)-1</math>.
+
|
 +
::<math style="vertical-align: -13px">\int \tan^4(x)~dx=\int \tan^2(x) \tan^2(x)~dx.</math>
 +
|-
 +
|Using the trig identity <math style="vertical-align: -5px">\sec^2(x)=\tan^2(x)+1,</math> we have  
 +
|-
 +
|
 +
::<math style="vertical-align: -5px">\tan^2(x)=\sec^2(x)-1.</math>
 
|-
 
|-
|Plugging in the last identity into one of the <math style="vertical-align: -5px">\tan^2(x)</math>, we get
+
|Plugging in the last identity into one of the <math style="vertical-align: -5px">\tan^2(x),</math> we get
 
|-
 
|-
| &nbsp;&nbsp; <math style="vertical-align: -13px">\int \tan^4(x)~dx=\int \tan^2(x) (\sec^2(x)-1)~dx=\int \tan^2(x)\sec^2(x)~dx-\int \tan^2(x)~dx=\int \tan^2(x)\sec^2(x)~dx-\int (\sec^2x-1)~dx</math>,
+
|
 +
::<math>\begin{array}{rcl}
 +
\displaystyle{\int \tan^4(x)~dx} & = & \displaystyle{\int \tan^2(x) (\sec^2(x)-1)~dx}\\
 +
&&\\
 +
& = & \displaystyle{\int \tan^2(x)\sec^2(x)~dx-\int \tan^2(x)~dx}\\
 +
&&\\
 +
& = & \displaystyle{\int \tan^2(x)\sec^2(x)~dx-\int (\sec^2x-1)~dx.}\\
 +
\end{array}</math>
 
|-
 
|-
 
|using the identity again on the last equality.
 
|using the identity again on the last equality.
Line 42: Line 61:
 
!Step 2: &nbsp;
 
!Step 2: &nbsp;
 
|-
 
|-
|So, we have <math style="vertical-align: -13px">\int \tan^4(x)~dx=\int \tan^2(x)\sec^2(x)~dx-\int (\sec^2x-1)~dx</math>.
+
|So, we have  
 +
|-
 +
|
 +
::<math style="vertical-align: -13px">\int \tan^4(x)~dx=\int \tan^2(x)\sec^2(x)~dx-\int (\sec^2x-1)~dx.</math>
 
|-
 
|-
|For the first integral, we need to use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -5px">u=\tan(x)</math>. Then, <math style="vertical-align: -5px">du=\sec^2(x)dx</math>.
+
|For the first integral, we need to use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -5px">u=\tan(x).</math> Then, <math style="vertical-align: -5px">du=\sec^2(x)dx.</math>
 
|-
 
|-
 
|So, we have
 
|So, we have
 
|-
 
|-
| &nbsp;&nbsp; <math style="vertical-align: -13px">\int \tan^4(x)~dx=\int u^2~du-\int (\sec^2(x)-1)~dx</math>.
+
|
 +
::<math style="vertical-align: -13px">\int \tan^4(x)~dx=\int u^2~du-\int (\sec^2(x)-1)~dx.</math>
 
|}
 
|}
  
Line 56: Line 79:
 
|We integrate to get  
 
|We integrate to get  
 
|-
 
|-
| &nbsp;&nbsp; <math style="vertical-align: -13px">\int \tan^4(x)~dx= \frac{u^3}{3}-(\tan(x)-x)+C=\frac{\tan^3(x)}{3}-\tan(x)+x+C</math>.
+
|  
 +
::<math>\begin{array}{rcl}
 +
\displaystyle{\int \tan^4(x)~dx} & = & \displaystyle{\frac{u^3}{3}-(\tan(x)-x)+C}\\
 +
&&\\
 +
& = & \displaystyle{\frac{\tan^3(x)}{3}-\tan(x)+x+C.}\\
 +
\end{array}</math>
 
|}
 
|}
  

Revision as of 14:03, 18 April 2016

Evaluate the integral:


Foundations:  
Recall:
1.
2.
How would you integrate
You could use -substitution. Let Then, Thus,


Solution:

Step 1:  
First, we write
Using the trig identity we have
Plugging in the last identity into one of the we get
using the identity again on the last equality.
Step 2:  
So, we have
For the first integral, we need to use -substitution. Let Then,
So, we have
Step 3:  
We integrate to get
Final Answer:  
  

Return to Sample Exam